Studia lexicologica - Filipec, Josef (Peter Lang International Academic Publishers, 2021)
The Czech linguist Josef Filipec, with his many groundbreaking works, has not only established the modern lexicology and lexicography of the Czech language, but has also made significant contributions to general lexicology, which are still too little known outside of Slavic studies. The contributions collected here provide a welcome insight into the author's long-standing findings and are based on rare, mutually stimulating interactions of practical work on the dictionary (see the recent work "Slovnik spisovné češtiny pro školu a veřejnost", 1994). and the theoretical generalization (see the basic work "Česká lexikologie", together with F. Cermák, 1995).